Leadership style, work motivation and organizational commitment among trainers in the Center of Excellence Malaysian Armed Forces (MAF) - Wan Othman, Wan Norhayati; Abdullah, Mohd Yusuf; Abdul Rahman, Mohd Ghazali; Zainuddin, Zaida Nor; Mohamad Yusop, Yusni (Pennwell, 2020)
Organizational commitment is the sense and trust of the organization that it belongs to. A person who is committed to his or her organization will always be confident and pleased in the organization and willing to do whatever is considered good to the organization. The purpose of this study was to analyze the influence of leadership style as well as work motivation with organizational commitment among trainers in Center of Excellence, Malaysian Armed Force (MAF). The results show that there is a positive and significant relationship between transformational leadership style and work motivation towards organizational commitment. The findings also show that transformational leadership and work motivation influenced the organizational commitment among the trainers. Therefore, this study is greatly useful to the Ministry of Defense Malaysia to ensure that the trainers at the MAF Center of Excellence achieve high job satisfaction in order to continue committing to the organization to produce good and excellent services.